EFEK ANTI INFLAMASI KITOSAN DARI CANGKANG UDANG PANTAI TRISIK PADA TIKUS MODEL RHEUMATOID ARTHRITIS - Hanifah, Nurul; Darmawan, Endang (Pharmaciana, 2015)
This research was conducted to investigate the effect of chitosan as anti-inflammatory in rheumatoid arthritic in reduction of paw edema using plethysmometer. Chitosan was isolated from the shrimp shell on the Trisik Coastal were administered orally on 17-32th day with CMC 0,5%. This research using repeated measure design. To evaluate anti-inflammatory effect of the suspension, an arthritic rats model was developed using Complete Freund`s Adjuvant (CFA) on 1-16th day. In addition, the research was divided into 5 groups (n=6) including normal control groups, positive control groups, negative control groups, 1 group were treated by chitosan suspension at 50 mg/200 gram BW doses and the other group were treated by chitosan suspension at 100 mg/200 gram BW doses. The reduction of paw edema were determined every 3 day after 17th days then analyzed using general linear repeated measure test (p<0,05). The results showed that paw edema of arthritic rats were evidently decreased by chitosan suspension at 100 mg/200 gram BW doses (142,66%) better than chitosan suspensionÂ  at 50 mg/200 gram BW doses (117,23%). In conclusion, the chitosan from shrimp shell of Trisik coastal is found to be effective as anti-inflammatory in rheumatoid arthritic rats model.